Cichorium intybus L. Oligo-Polysaccharides (CIO) Exerts Antianxiety and Antidepressant Effects on Mice Experiencing Behavioral Despair and Chronic Unpredicted Mild Stress - Yanqin Luo; Xueyi Bei; Yiwen Zhang; Xinran Sun; Yongzhi Zhao; Fang Chen; Ruile Pan; Qi Chang; Qinghu He; Xinmin Liu; Ning Jiang (Foods)
Cichorium intybus L. oligo-polysaccharides (CIOs), obtained from Cichorium intybus L., is a mixture of oligosaccharides and polysaccharides. This study explores the antianxiety and antidepressant effects and mechanisms of CIOs by using acute behavioral despair and chronic unpredictable mild stress mice models and measuring the levels of 5-HT and the expression of proteins related to the BDNF/ERK and PI3K/Akt/mTOR pathways. Moreover, 56 male C57BL/6N mice were used to test behavioral despair. They were randomized into seven groups (Control, Citalopram, CIO 12.5 mg/kg, CIO 25 mg/kg, CIO 100 mg/kg, and CIO 200 mg/kg) based on body weight; they were administered with the corresponding medication daily for 7 days; and behavioral tests were conducted on them (forced swimming test (FST) and tail suspension test (TST)) after 7 days. Seventy male C57BL/6N mice were adopted in the next part of the experiment and randomly divided into seven groups (Control, CUMS, Fluoxetine, MOO, CIO 25 mg/kg, and CIO 100 mg/kg) based on the sucrose preference index. Except for the control group, the other groups were subjected to 6 weeks of CUMS. From the fifth week of stress, the corresponding drugs were administered by gavage until the end of the behavioral tests. In the behavioral despair tests, the immobility time was significantly reduced in the FST and TST after the CIO (25 and 100 mg/kg) treatment of 7 days. After 6 weeks of chronic unpredicted mild stress (CUMS) treatment, CIO (25, 50, and 100 mg/kg) administration significantly reduced the number of buried beads in the marble burying test (MBT), decreased the latency in the novelty-suppressed feeding test (NSFT), and shortened the immobility time in the FST and TST. CIO administration significantly increased the sucrose preference index in the sucrose preference test (SPT). Additionally, CIO treatment increased hippocampal 5-HT levels while upregulating the expression of BDNF, P-PI3K/PI3K, P-ERK/ERK, P-Akt/Akt, and P-mTOR/mTOR. In summary, CIO exerted promising antidepressant effects in behavioral despair and antianxiety and antidepressant effects in CUMS-induced depressive mice. Moreover, CIO therapy was facilitated by increasing the 5-HT content, alleviating the damage of hippocampal neurons, and upregulating the BDNF/ERK and PI3K/AKT/mTOR cascade. Thus, CIO is a substance with the potential to treat anxiety and depression.